Debunking the Stereotype of the Lazy Welfare Recipient: Evidence from Cash Transfer Programs. (30th August 2017) - Banerjee, Abhijit V.; Hanna, Rema; Kreindler, Gabriel E.; Olken, Benjamin A.
Abstract: Targeted transfer programs for poor citizens have become increasingly common in the developing world. Yet, a common concern among policy-makers and citizens is that such programs tend to discourage work. We re-analyze the data from seven randomized controlled trials of government-run cash transfer programs in six developing countries throughout the world, and find no systematic evidence that cash transfer programs discourage work.